(L, M)-fuzzy topological spaces - Matutu, Phethiwe Precious (Rhodes University, Faculty of Science, Department of Mathematics, 1992)
The objective of this thesis is to develop certain aspects of the theory of (L,M)-fuzzy topological spaces, where L and M are complete lattices (with additional conditions when necessary). We obtain results which are to a large extent analogous to results given in a series of papers of SÌŒostak (where L = M = [0,1]) but not necessarily with analogous proofs. Often, our generalizations require a variety of techniques from lattice theory e.g. from continuity or complete distributive lattices.
Keywords: Topological spaces; Fuzzy sets